ONLINE INSTRUCTIONAL STRATEGIES FOR ENGLISH LANGUAGE LEARNING DURING COVID-19 PANDEMIC: A CASE FROM A CREATIVE TEACHER - Abdul Halim; Sunarti Sunarti (JOALL (Journal of Applied Linguistics and Literature), 2021)
This paper aimed at discussing online instructional strategies and learning quadrant for English language learning during COVID-19 pandemic. Therefore, the current paper reviews possible instructional strategies and learning quadrant used by a teacher in the teaching process from online platforms to ensure the educational goals are plausible to be achieved, although without having to attend classrooms regularly, especially during the COVID-19 outbreak that happens during 2019-2020. Employing qualitative design, the study involved one teacher and 34 students. The data were collected through observation and interviews with the participants. The data analysis involved data coding, data description and data assertion. The results showed that although the participants did not attend a physical classroom, the learning process with various approaches for learning and assessments were still possible to engage the students.